2017
DOI: 10.4236/asm.2017.71004
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Use in Ghana: What about Women Empowerment?

Abstract: Introduction: Although contraceptive usage appears to be increasing in Ghana, 30 and 42 percent of married and unmarried women respectively still have unmet need for family planning services partly due to their inability to exercise their basic rights on fertility issues. Meanwhile, expanding freedom of choice and actions to shape women's life is critical to how women can be autonomous about issues surrounding their fertility. On this premise, this study aimed at investigating empowerment status and usage of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
4
15
0
Order By: Relevance
“…We also looked at how socio-demographic factors influence IPV among Women in Sub-Saharan Africa. Our study found an overall prevalence of IPV of 37% and this is consistent with findings of previous studies on the prevalence of IPV in Sub-Saharan region [ 1 , 25 , 31 ]. These previous however included the general regions in Africa but our study considered only women in Sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 93%
“…We also looked at how socio-demographic factors influence IPV among Women in Sub-Saharan Africa. Our study found an overall prevalence of IPV of 37% and this is consistent with findings of previous studies on the prevalence of IPV in Sub-Saharan region [ 1 , 25 , 31 ]. These previous however included the general regions in Africa but our study considered only women in Sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 93%
“…However, only a quarter of women in this study took healthcare decisions alone. This is in line with the findings of previous studies in Ghana [27,50]. We realised that women who take healthcare decisions alone were less likely to seek healthcare for childhood illnesses, compared to those who did not decide alone.…”
Section: Discussionsupporting
confidence: 92%
“…In low- and middle-income countries, particularly sub-Saharan Africa and Southern Asia, there are several socio-economic and cultural factors which affect women’s ability to make decision regarding their own health and those of their dependents, especially children [14,15]. Earlier studies have focused on some aspects of reproductive health, women autonomy and decision-making, using sub-populations within some countries in sub-Saharan Africa [5,10,16,17,18,19,20]. As far as we know, no study has investigated the subject in multiple countries in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Decision making is a process that starts with problem identification, data collection and gathering, analysis of data, findings, selecting an appropriate and most suitable solution from the alternative solutions and finally evaluation of the process [23]. Socio-demographic characteristics such as level of education [5], partner educational level [5, 10] and wealth status [10, 16] have the potential of influencing an individual in making informed decision. Exposure to information and knowledge and the ability to provide for one’s needs is a positive influence on decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation